The Regional Importance of Oxygen Demand and Supply for Historical Ocean Oxygen Trends - Pearse James Buchanan; Alessandro Tagliabue (Geophysical Research Letters)
Abstract Ocean deoxygenation is an emerging hazard for marine ecosystems and a fingerprint of anthropogenic change. Interior ocean oxygen concentrations respond to changes in ventilation that supply oxygen and the demand of biogeochemical processes that consume oxygen. A better understanding of their regional importance would improve confidence in Earth System Model projections, which underpin ecosystem risk and vulnerability assessments. Using a hindcast reanalysis simulation, we find that oxygen trends between 1975 and 2014 in low‐oxygen zones along eastern margins are strongly affected by biogeochemical processes that alter oxygen demand, while oxygen‐rich regions of the open ocean are driven by ventilation changes. A similar regional distinction emerges among CMIP6 Earth System Models. Therefore, while biogeochemical functioning is an important source of uncertainty in low‐latitude, low‐oxygen regions, uncertainty in global trends is due to insufficient physical supply changes in Earth System Models, which is confirmed using repeat hydrographic section data in the southern mid‐latitudes.